PERAN PENDIDIKAN PANCASILA DAN KEWARGANEGARAAN DALAM MENERAPKAN KARAKTER MANDIRI SISWAKELAS XI IPS I MADRASAH ALIYAH MATHLA’UL ANWAR KEPUH CINANGKA - E. Nita Prianti; Laila Novia Rahman (Pendidikan Pancasila dan Kewarganegaraan, FKIP, Universitas Banten Jaya, 2019)
This study aims to determine how the role of Pancasila education and citizenship in applying the independent character of students in class XI IPS 1 MA Mathla'ul Anwar Head of Cinangka, and to find out the supporting and inhibiting factors in applying the independent character of students.This study uses descriptive research methods and qualitative approaches, the subject of this research is PPKn teachers totaling 2 people and class XI students totaling 10. Data collection through interviews, observation and documentation. Data were analyzed by steps of data reduction, data display, and conclusion drawing.The results of this study indicate that: (1) PPKn has a very important role for the application of students' independent character because PPKn does not teach the values ​​of independent characters that are embedded, among them are responsiveness, no dependence on others, self-confidence, creativity, controlling yourself, make your own decisions and overcome your own problems. (2) The supporting factor is the desire of students, diversity, teachers, and parents while the inhibiting factors are the teacher's personality, school environment and bad habits as well as the adverse effects of parental treatment conditions. (3) efforts to make students apply the students' independent character, namely by collaborating between schools such as teachers, homeroom teachers, principals and parents.